A new species of Satanoperca (Teleostei: Cichlidae) from the Rio Tocantins basin, Brazil - Ota,Renata Rúbia (2021)
Abstract A new species of Satanoperca is described from the Rio Araguaia, Rio Tocantins basin, Brazil, and non-native records are available in the upper Rio Paraná basin. It differs from congeneric species by color pattern characters, such as head and flank marks. It is included in the Satanoperca jurupari species group, characterized by the absence of black rounded blotches on the flank, and low meristic values. A description of the ontogeny of melanophore marks of the S. jurupari species group revealed two different types of arrangement on the flank and numerous melanophore marks on the head. A discussion on morphologically diverse assemblages in the S. jurupari species group is also provided.